Implementasi Progam One Stop Service (Pelayanan Terpadu Satu Pintu) pada Masyarakat Miskin (Studi Deskriptif dalam Pengurusan Dokumen Diri di Desa Kajarharjo, Kecamatan Kalibaru, Kabupaten Banyuwangi) - Agusta, Moh Rizqi; A, Arif (University of Jember, 2017)
Abstract Kajarharjo was one of the villages in Banyuwangi that had a lot of poor people who did not have personal documents like Electronic Identification Card, Family Certificate and Birth Certificate because its management was complicated, expensive, and discriminating to the poor community. Therefore, the government issued a one-stop integrated service program. The research problem was how the implementation of one-stop integrated service program in poor community is. The used research method was descriptive with qualitative approach. The research location was in Kajarharjo village, Kalibaru subdistrict, Banyuwangi regency. The used informant determination technique was purposive with principal and additional informants. The data were collected by using semi-structured interview technique, participatory observation, and documentation. To test the data validity, the researcher used triangulation of data sources. The research result was the implementation of one-stop integrated service program was suitable with the standard of the program without distinguishing the economic status, and the poor community could access the social welfare program because they had complete personal documents.